2D Seismic Structural Study of the Area Between Halfaya, Noor and Amara Oil Fields, Southeastern Iraq - Al-Azzawi, Bakr Samar; Ali, Kamal K. (Iraqi Journal of Science, 2024)
The study area is located in the Missan government in southeastern Iraq, including oilfields (Halfaya, Noor, and Amara). The study area is about 966 Km2. Based on the 2D seismic reflection interpretation, well-logs data (sonic and estimated density logs), and synthetic seismogram of well Am-2, two horizons were identified and picked (Nahr Umr and Shuaiba) within the Lower Cretaceous age. For the picked reflectors, two-way time and depth maps were created to display the subsurface's structural makeup. The structural interpretation shows two structural axes in the study area. The first is the Halfaya-Amara axis, whose direction is WNW-ESE corresponding with the Amara structure. This axis deviates southeast due to the tectonic effect at the Halfaya structure. Another tectonic force affected the Halfaya structure in the northwest-southeast direction leading to the appearance of a branch of a convex extension towards the north from the middle of the Halfaya structure, completing this branch to a structural closure as nose towards the Noor structure in the northern part of the study area. The second axis of Halfaya-Noor oilfields trending northwest-southeast direction.